Evaluasi Kinerja Steam Jet Ejector Tingkat Pertama Terhadap Kevakuman Kondensor - Melkias, Alvera Apridalianti; Nuno Gomez, Shahrul (Fakultas Teknik UMRI, 2024)
The steam jet ejector is a device for extracting NCG from the condenser. NCG can increase the pressure in the condenser until a vacuum condition is not reached. The diffuser pressure on the steam jet ejector has a normal operational limit of below 1 atm, meaning that the ejector performance will be optimal if it is operated at the operational limit under vacuum conditions. The expected objectives are to determine the effect of the steam jet ejector on condenser vacuum, calculate the performance of the first level steam jet ejector through pressure analysis in the diffuser section, calculate the performance of the steam jet ejector in actual conditions compared to the design data conditions and analyze actions that can be taken to improve the performance of the tool. Based on the results of calculations and analysis, it was found that the increase in steam jet ejector pressure had an effect on the increase in condenser pressure from the design pressure of 0.10 bar to 0.107-0.123 bar under actual conditions. The decrease in steam jet ejector performance results in the condenser vacuum level decreasing, but the equipment performance is within normal operational limit conditions, namely below 1 atm. The decrease in steam jet ejector performance is influenced by the motive steam mass flow rate, NCG mass flow towards suction, entrainment ratio value, NCG pressure and motive steam pressure which exceeds the design data.